Excessive adiposity and sedentary lifestyles are prevalent in cancer patients: a pilot study - Ana Isabel Almeida; Dina Raquel João; Andreia Rolão; Isabel Monteiro-Grillo; Maria Camilo; Paula Ravasco (Nutrición Hospitalaria, 2013)
Cancer aetiology is multifactorial; risk factors comprise obesity, central adiposity, physical inactivity and excessive/deficient intake of foods and/or nutrients with pro-carcinogenic/protective effects. We aim to analyze the pattern of nutritional status, food intake and physical activity in a cohort of cancer patients. This pilot cross-sectional study was conducted in 64 outpatients referred for Radiotherapy. Nutritional parameters evaluated: BMI, waist circumference, body composition by tetrapolar bioimpedance (Xitron®). Usual food intake was collected with a short food frequency questionnaire and physical activity was assessed with Jacksons' questionnaire. Overweight/obesity and excessive body fat mass prevalence was of 53% and 61%, respectively. Central obesity, which indicates moderate/high cardio-metabolic risk, was found in 78% of patients. Food frequency analysis showed a poor intake in vegetables and a high intake in meat and carbohydrates. Physical inactivity was prevalent. This pilot study in cancer patients, showed a high prevalence of overweight/obesity, excessive fat mass and central obesity, simultaneously with sedentary lifestyles and an inadequate diet, poor in protective foods and excessive in deleterious ones. Thus, these patients exhibit a high risk pattern for cancer development and for a poorer prognosis. The implementation of measures to promote balanced and protective diets and to encourage physical activity practice is urgently needed.